PCR ANALYSIS IN THE REAL TIME REGIMEN AS A LONG-TERM METHOD FOR LABORATORY DIAGNOSIS OF RICKETTSIOSIS - E. E. Alieva; E. I. Bondarenko; M. T. Gafarova; K. D. Malyi; E. A. Verbenets (Инфекция и иммунитет, 2018)
.